2023
DOI: 10.1002/jso.27228
|View full text |Cite
|
Sign up to set email alerts
|

Patient and caregiver experience with telehealth for surgical cancer care: A qualitative study

Abstract: Introduction The COVID‐19 pandemic led to telemedicine adoption for many medical specialties, including surgical cancer care. To date, the evidence for patient experience of telemedicine among patients with cancer undergoing surgery is limited to quantitative surveys. Thus, this study qualitatively assessed the patient and caregiver experience of telehealth visits for surgical cancer care. Methods We conducted semistructured interviews with 25 patients with cancer and three caregivers who had completed a teleh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Clinicians and patients were congruent in expressing convenience, safety and improved access to care as benefits of telehealth, consistent with previously reported research 18,20,23,41 . Patients also reported that telehealth allowed family and friends to be present in a supportive role during the consultation, without a major impact on the family member/friend's routines.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Clinicians and patients were congruent in expressing convenience, safety and improved access to care as benefits of telehealth, consistent with previously reported research 18,20,23,41 . Patients also reported that telehealth allowed family and friends to be present in a supportive role during the consultation, without a major impact on the family member/friend's routines.…”
Section: Discussionsupporting
confidence: 81%
“…This was echoed by the clinicians—most felt comfortable during telehealth consultations and believed that they delivered an adequate service, while still expressing a strong preference for face‐to‐face consultations. These views are consistent with those of other cancer patients 12 , 15 , 16 , 18 , 20 , 21 , 22 , 41 and their clinicians, 14 , 15 , 18 , 41 which suggests that telehealth cannot replace face‐to‐face consultations.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations